Comprehensive Technical Inspection of a Medieval Bridge (Ponte de Vilanova, in Allariz) Using Microtechnological Tools - Rubén Rodríguez Elizalde (Eng)
Ponte de Vilanova, a masonry bridge, was built in Allariz, Galicia in the 13th–14th centuries. It is still standing. The structure, generally well preserved, shows minor deformations and wear signs caused by environmental factors. To conduct a comprehensive assessment without impacting the bridge’s integrity, drones equipped with thermal and underwater imaging technology were employed. Aerial inspections revealed vegetation growth and minor efflorescence (salt deposits) in some areas, while aerial thermography detected temperature variations along the stone joints, indicating the presence of moisture. The granite blocks comprising the bridge showed consistent quality and preservation. The underwater inspection confirmed that the bridge’s piers are well set on the riverbed, with no major damage observed, ruling out the immediate need for repair. This approach allowed a thorough evaluation of submerged parts without requiring divers, enhancing safety and reducing costs.